English for Specific Purpose: Revitalizing Climate Change Awareness Using Digital Literacy and Gamification for Engineering Faculty in Papua - Martha Betaubun; Nasrawati Nasrawati (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
The air quality index (AQI) in Papua has the best index among other provinces in Indonesia. Papua has different geographical and social conditions than western Indonesia. In particular, forests in Papua are more numerous with fewer industries and automobiles than provinces in western Indonesia. The article aims to determine respondents' perceptions related to climate change awareness and pro-environmental behavior (PEB) in regions that have AQI in Indonesia, namely Papua. This study uses a survey strategy through a questionnaire instrument for students who have received the application of digital literacy and gamification in the English for Specific Purposes class. The questionnaire was distributed to be filled in by respondents with a total number of responses totaling 164 responses from students of engineering faculty. This study identified that respondents' awareness of climate change was in the moderately aware category (M = 3.8). These findings are directly proportional to PEB respondents who are at the middle level (M = 3.9). Furthermore, analysis of the data shows that respondents are highly aware (M = 4.3) that humans have a responsibility for climate change, and respondents are highly concern (M = 4.4) to carry out forestation both by individuals and community. The finding implication of this study is learning through digital literacy and gamification has a positive potential to be applied through policy and developed into a learning model to increase awareness of climate change and PEB. Keywords: Climate Change, Pro-environmental Behavior, Digital Literacy, Englsih for Specific Puprposes